Synthesis of carbon nanowalls from a single-source metal-organic precursor - Giese, André; Schipporeit, Sebastian; Buck, Volker; Wöhrl, Nicolas (Beilstein Journal of Nanotechnology, 2018)
In this work, the deposition of carbon nanowalls (CNWs) by inductively coupled plasma enhanced chemical vapor deposition (ICP-PECVD) is investigated. The CNWs are electrically conducting and show a large specific surface area, which is a key characteristic to make them interesting for sensors, catalytic applications or energy-storage systems. It was recently discovered that CNW films can be deposited by the use of the single-source metal-organic precursor aluminium acetylacetonate. This precursor is relatively unknown in combination with the ICP-PECVD deposition method in literature and, thus, based on our previous publication is further investigated in this work to better understand the influence of the various deposition parameters on the growth. Silicon, stainless steel, nickel and copper are used as substrate materials. The CNWs deposited are characterized by scanning electron microscopy (SEM), Raman spectroscopy and Auger electron spectroscopy (AES). The combination of bias voltage, the temperature of the substrate and the substrate material had a strong influence on the morphology of the graphitic carbon nanowall structures. With regard to these results, a first growth model for the deposition of CNWs by ICP-PECVD and aluminium acetylacetonate is proposed. This model explains the formation of four different morphologies (nanorods as well as thorny, straight and curled CNWs) by taking the surface diffusion into account. The surface diffusion depends on the particle energies and the substrate material and thus explains the influence of these parameters.
Keywords: aluminium acetylacetonate; carbon nanowalls; growth zones; ICP PECVD; metal-organic precursor

(untitled) - Wu, Y.; Qiao, P.; Chong, T.; Shen, Z. (Adv. Mater., 2002)

(untitled) - Stancu, E. C.; Ionita, M. D.; Vizireanu, S.; Stanciuc, A. M.; Moldovan, L.; Dinescu, G. (Mater. Sci. Eng., B, 2010)

(untitled) - Shang, N. G.; Papakonstantinou, P.; McMullan, M.; Chu, M.; Stamboulis, A.; Potenza, A.; Dhesi, S. S.; Marchetto, H. (Adv. Funct. Mater., 2008)

(untitled) - Hiramatsu, M.; Hori, M. (Jpn. J. Appl. Phys., 2006)

(untitled) - Nishimura, K.; Jiang, N.; Hiraki, A. (IEICE Trans. Electron., 2003)

(untitled) - Wu, Y.; Yang, B.; Zong, B.; Sun, H.; Shen, Z.; Feng, Y. (J. Mater. Chem., 2004)

New Progress on Graphene Research - Zheng, W.; Shen, B.; Zhai, W. (Surface functionalization of graphene with polymers for enhanced properties, 2013)

(untitled) - Lackner, G.; Mayer-Uhma, T.; Endler, I.; Boucher, R.; Meissner, F.; Scholz, S.; Krug, M.; Bezugly, V.; Mkandawire, M.; Majumder, A. (J. Mater. Sci. Eng. B, 2012)

(untitled) - Bo, Z.; Yang, Y.; Chen, J.; Yu, K.; Yan, J.; Cen, K. (Nanoscale, 2013)

(untitled) - Chul Shin, S.; Yoshimura, A.; Matsuo, T.; Mori, M.; Tanimura, M.; Ishihara, A.; Ota, K.-i.; Tachibana, M. (J. Appl. Phys., 2011)

(untitled) - Yu, K.; Bo, Z.; Lu, G.; Mao, S.; Cui, S.; Zhu, Y.; Chen, X.; Ruoff, R. S.; Chen, J. (Nanoscale Res. Lett., 2011)

New Progress on Graphene Research - Hiramatsu, M.; Kondo, H.; Hori, M. (Graphene nanowalls, 2013)

(untitled) - Gao, D.; Li, M.; Li, H.; Li, C.; Zhu, N.; Yang, B. (J. Solid State Electrochem., 2017)

(untitled) - Kwon, S. H.; Kim, H. J.; Choi, W. S.; Kang, H. (J. Nanosci. Nanotechnol., 2018)

(untitled) - Liu, X.; Wang, D.; Zhang, B.; Luan, C.; Qin, T.; Zhang, W.; Shi, X.; Deng, T.; Zheng, W. (Electrochim. Acta, 2018)

(untitled) - Krivchenko, V.; Shevnin, P.; Pilevsky, A.; Egorov, A.; Suetin, N.; Sen, V.; Evlashin, S.; Rakhimov, A. (J. Mater. Chem., 2012)

(untitled) - Vizireanu, S.; Ionita, M. D.; Dinescu, G.; Enculescu, I.; Baibarac, M.; Baltog, I. (Plasma Processes Polym., 2012)

(untitled) - Kondo, S.; Kawai, S.; Takeuchi, W.; Yamakawa, K.; Den, S.; Kano, H.; Hiramatsu, M.; Hori, M. (J. Appl. Phys., 2009)

(untitled) - Liu, R.; Chi, Y.; Fang, L.; Tang, Z.; Yi, X. (J. Nanosci. Nanotechnol., 2014)

(untitled) - Cheng, C. Y.; Teii, K. (IEEE Trans. Plasma Sci., 2012)

(untitled) - Zhu, M.; Wang, J.; Holloway, B. C.; Outlaw, R. A.; Zhao, X.; Hou, K.; Shutthanandan, V.; Manos, D. M. (Carbon, 2007)

(untitled) - Malesevic, A.; Vitchev, R.; Schouteden, K.; Volodin, A.; Zhang, L.; van Tendeloo, G.; Vanhulsel, A.; van Haesendonck, C. (Nanotechnology, 2008)

(untitled) - Jain, H. G.; Karacuban, H.; Krix, D.; Becker, H.-W.; Nienhaus, H.; Buck, V. (Carbon, 2011)

Synthesis and characterization of carbon nanowalls by ICP-CVD using aluminium-acetylacetonate precursor - Jain, H. G. (Universität Duisburg-Essen, 2012)

(untitled) - Hargis, P. J.; Greenberg, K. E.; Miller, P. A.; Gerardo, J. B.; Torczynski, J. R.; Riley, M. E.; Hebner, G. A.; Roberts, J. R.; Olthoff, J. K.; Whetstone, J. R.; van Brunt, R. J.; Sobolewski, M. A.; et al. (Rev. Sci. Instrum., 1994)

Diagnostics and modeling of an inductively coupled radio frequency discharge in hydrogen - Kadetov, V. A. (Ruhr-Universität Bochum, 2004)

(untitled) - Siddiqi, M. A.; Siddiqui, R. A.; Atakan, B. (Surf. Coat. Technol., 2007)

(untitled) - Nielsen, G. F.; Silva, L. H. F.; Cruz, N. C.; Rangel, E. C. (Surf. Interface Anal., 2013)

(untitled) - Ferrari, A. C.; Meyer, J. C.; Scardaci, V.; Casiraghi, C.; Lazzeri, M.; Mauri, F.; Piscanec, S.; Jiang, D.; Novoselov, K. S.; Roth, S.; Geim, A. K. (Phys. Rev. Lett., 2006)

(untitled) - Casiraghi, C.; Pisana, S.; Novoselov, K. S.; Geim, A. K.; Ferrari, A. C. (Appl. Phys. Lett., 2007)

(untitled) - Gan, Y.; Sun, L.; Banhart, F. (Small, 2008)

(untitled) - Uchida, T.; Baliyan, A.; Fukuda, T.; Nakajima, Y.; Yoshida, Y. (RSC Adv., 2014)

(untitled) - Krivchenko, V. A.; Evlashin, S. A.; Mironovich, K. V.; Verbitskiy, N. I.; Nefedov, A.; Wöll, C.; Kozmenkova, A. Y.; Suetin, N. V.; Svyakhovskiy, S. E.; Vyalikh, D. V.; Rakhimov, A. T.; Egorov, A. V.; et al. (Sci. Rep., 2013)

(untitled) - Kurita, S.; Yoshimura, A.; Kawamoto, H.; Uchida, T.; Kojima, K.; Tachibana, M.; Molina-Morales, P.; Nakai, H. (J. Appl. Phys., 2005)

(untitled) - Ferrari, A. C.; Robertson, J. (Philos. Trans. R. Soc. London, Ser. A, 2004)